Technology Acceptance Model to Factors Customer Switching on Online Shopping Technology: Literature Review - Setyoadi, Eddy Triswanto; Rahmawati, Titasari (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Customer loyalty is a phenomenon that is the center of attention of an organization or company because it greatly influences the continuity and development of the organization. Customers are said to be loyal if they have affection for a company's products or services. So that loyal customers will express this affection by saying positive things about the company's products or services to friends, relatives and co-workers. However, if customers feel uncomfortable with a company's products and services, there is a possibility that customers will switch from loyal to disloyal. This is usually called customer switching. This research is based on a systematic review of the influence of usability and ease of use of online shopping applications as well as the factors causing customers to switch from online shopping applications to mobile retail applications. Three phases are used in this study's systematic literature review (SLR). The factors that were discovered were categorized using three main themes. Interconnected among these three elements are perceived utility, perceived ease of use, and behavioral intention to use. This study also found that when TAM is added as a new component to gauge the intention to adopt an online shopping application, "trust, ease, and information quality" are the most important factors. By carefully identifying the effects of online shopping application on business management, this research contributes theory. The findings assist online shopping application service providers in formulating sensible plans for foreseeing and enhancing clients' intentions to use online shopping applications.